1978
DOI: 10.1111/j.1471-4159.1978.tb07831.x
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Gaba Metabolism and Met‐enkephalin Content in Rat Brain Following Repeated Electroconvulsive Shocks

Abstract: The effects of electroconvulsive shock (ECS; 120 V for 1 s through ear‐clip electrodes) or sub‐convulsive shocks (70 V for 1 s) on rat brain GABA and met‐enkephalin concentration and GABA turnover has been examined 24 h after a single treatment (×1) or once daily for 10 days (×10). ECS × 10 increased GABA concentrations in the N. caudatus and N. accumbens and decreased the synthesis rate of GABA by 40% and 50% respectively in these regions. Sub‐convulsive shocks (× 10 × 10) or ECS × 1 had no effect. No consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0

Year Published

1984
1984
1990
1990

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(24 citation statements)
references
References 23 publications
4
20
0
Order By: Relevance
“…), three times higher than the dose used in this study, produced no further increase in GABA accumulation in either cortex, hippocampus or striatum 40 min after injection compared with the lower dose, thereby confirming that the lower dose of 10mgkg-' employed throughout, caused maximal inhibition of GABA-transaminase (GABA-T) activity and thus virtually complete attenuation ofthe catabolism of GABA. A final reason for confidence in the current technique for evaluation of GABA synthesis is that using this method essentially identical data were obtained on GABA synthesis rates following repeated seizures as those obtained with a gas chromatographic-mass spectrometric technique (Green et al, 1978).…”
Section: Discussionmentioning
confidence: 87%
“…), three times higher than the dose used in this study, produced no further increase in GABA accumulation in either cortex, hippocampus or striatum 40 min after injection compared with the lower dose, thereby confirming that the lower dose of 10mgkg-' employed throughout, caused maximal inhibition of GABA-transaminase (GABA-T) activity and thus virtually complete attenuation ofthe catabolism of GABA. A final reason for confidence in the current technique for evaluation of GABA synthesis is that using this method essentially identical data were obtained on GABA synthesis rates following repeated seizures as those obtained with a gas chromatographic-mass spectrometric technique (Green et al, 1978).…”
Section: Discussionmentioning
confidence: 87%
“…In recent years the involvement of y-aminobutyric acid (GABA) in the changes induced by stressful stimuli has also been assessed (Sherman & Gebhart, 1974;Green et al, 1978;Yoneda et al, 1983). The GABAergic system is known to modulate behaviour (Clement et al, 1987) and also to be influenced by environmental stimuli (Da Vanzo et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…An earlier study (Green et al, 1978) using mass fragmentography concluded that the elevated GABA concentration and decreased turnover data suggested that a decrease in GABA release was occurring in the striatum. This suggestion is supported by the current observations on K4-evoked release and it could be that it is the inhibition of release which is the change that initiates the other changes.…”
Section: Discussionmentioning
confidence: 99%
“…A later study by Bowdler et al (1983) confirmed and extended the observations that the GABA concentration changes in various brain regions following repeated ECS, but did not measure 'Author for correspondence; present address: Astra Neuro- The current studies have demonstrated that a single ECS or flurothyl-induced convulsion can induce marked changes in both GABA synthesis (Green et al, 1987a) and release (Green et al, 1987b) in regions of rat brain. An investigation has therefore been made of the effect of repeated seizures on GABA release in regions ofrat brain and on the rate ofGABA synthesis in various brain regions, the latter study being designed to try to confirm and extend an earlier investigation (Green et al, 1978) by use of a different methodology. In addition a study has been made of the activity of glutamic acid decarboxylate activity in rat brain both in the absence and presence of added cofactor (pyridoxal 5-phosphate), following repeated ECS since there is one report that activity is increased following repeated seizures (Atterwill et al, 1981).…”
Section: Introductionmentioning
confidence: 99%